Construction of Otherness: Links Between Immigration and Crime During the Cambiemos Administration (Argentina, 2015–2019) - Abiuso, Federico Luis (2023)
In December 2015, the political coalition Cambiemos won the national elections in Argentina, taking the candidate Mauricio Macri to the presidency for a period of four years. One of the recurring topics within public opinion during that time was the explicit and public reference to an alleged link between immigration and crime by administration officials of various kinds. Against this background, I propose to specifically address the ways in which the links between immigration and crime were defined in the political discourses implemented during the Cambiemos administration. The article presents different core categories, reconstructed through discourse analysis: (1) ‘we need to know who is who’; (2) distinction in the types of immigration that arrive in Argentina; (3) tighter controls on the conditions of entry into the country; and (4) crime and migration. In broader terms, and as the argumentative plotline, each of these core categories relates to the Cambiemos initiatives to manage ethnic and cultural diversity: identify, select, control and criminalise.